Photocatalytic degradation and adsorption of phenol by solvent-controlled TiO2 nanosheets assisted with H2O2 and FeCl3: Kinetic, isotherm and thermodynamic analysis - Zulfiqar, Muhammad (ELSEVIER, 2020)
Hydrofluoric acid (HF) has beenwidely employed to regulate the surface characteristics of TiO2 containing sheetlike morphology with (001) facets for various environmental applications. However, carcinogenic effects associated with HF are the main stumbling blocks on its way towards global commercialization. In the same line of action, an eco-friendly approach for the synthesis of anatase TiO2 nanosheets (TNSs) via employing hydrothermal process and N, N dimethylformamide (DMF) as a novelmorphology-controlling agent has been reported. The asproduced TNSs were characterized by XRD, HRTEM, Raman, FTIR, XPS and DRS characterizations. The photoactivity of as-produced TNSs was studied for photocatalytic degradation of phenol under visible light irradiation in the presence of green oxidants such as hydrogen peroxide (H2O2) and ferric chloride (FeCl3) toproduce free hydroxyl radicals for speedily reduction of recombination of photogenerated electrons hole-pairs. The results revealed that as-produced TNSs could activate by green oxidants with yielding up to 94.19 and 97.12% phenol degradation in the presence of H2O2 and FeCl3, respectively. Moreover, phenol adsorption data was well explained via pseudo first order and pseudo second order kinetics while Langmuir and Freundlich isotherms were more suitable to explain the adsorption of phenol onto TNSs, providing maximum adsorption capacity up to 23.596 mg/g. Various thermodynamic parameters were evaluated, suggesting the favourable, spontaneous and endothermic adsorption process. The values of activation energy (18.505 kJ/mol) confirmed the physical adsorption of phenol onto TNSs. The excellent aptitude of anatase TNSs to produce hydroxyl radicals and superoxides radicals with promptly lessening of recombination of photogenerated electron hole-pairs makes them motivated applicant for wastewater treatment. (C) 2020 Published by Elsevier B.V.